Effects of calorie labeling and value size pricing on fast food meal choices: Results from an experimental trial - Jeffery Robert W; Story Mary T; Oakes J Michael; French Simone A; Harnack Lisa J; Rydell Sarah A (BMC, 2008)
Abstract Background Although point-of-purchase calorie labeling at restaurants has been proposed as a strategy for improving consumer food choices, a limited number of studies have evaluated this approach. Likewise, little research has been conducted to evaluate the influence of value size pricing on restaurant meal choices. Methods To examine the effect of point-of-purchase calorie information and value size pricing on fast food meal choices a randomized 2 × 2 factorial experiment was conducted in which participants ordered a fast food meal from one of four menus that varied with respect to whether calorie information was provided and whether value size pricing was used. Study participants included 594 adolescents and adults who regularly ate at fast food restaurants. Study staff recorded the foods ordered and consumed by each participant. Participants also completed surveys to assess attitudes, beliefs and practices related to fast food and nutrition. Results No significant differences in the energy composition of meals ordered or eaten were found between menu conditions. The average energy content of meals ordered by those randomized to a menu that included calorie information and did not include value size pricing was 842 kcals compared with 827 kcals for those who ordered their meal from a menu that did not include calorie information but had value size pricing (control menu). Results were similar in most analyses conducted stratified by factors such as age, race and education level. Conclusion Additional research is needed to better evaluate the effects of calorie labeling and value size pricing on fast food meal choices. Studies in which participants are repeatedly exposed to these factors are needed since long term exposure may be required for behavior change.